Analysis of Characteristics and Turbulent Mixing of Seawater Mass in Lombok Strait - Amir Yarkhasy Yuliardi; Agus S. Atmadipoera; Gentio Harsono; Nyoman Metta N. Natih; Kentaro Ando (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2021)
The Lombok Strait, as one of the outlet straits, is part of the ITF route, which is directly adjacent to the Indian Ocean. There is a sill in the Lombok Strait, which is a place for internal wave generation. Leg-1 data from the Japan Agency for Marine-Earth Science and Technology in collaboration with the Agency for the Assessment and Application of Technology which is part of the Tropical Ocean Climate Study Expedition including CTD Yoyo and ADCP taken using ship vehicles R/V Kaiyo. CTD Snapshot from PUSHIDROSAL using the KRI Spica 934 vehicle part of the Opssurta Baruna Jaya 2 Expedition. Determination of seawater mass stratification with the criteria for the thermocline layer is ≥ 0.05 °C.m-1. Four types of water masses were identified, Java Sea, mixed seawater mass (Java Sea - ITF) which occurred diapycnal mixing, North Pacific Subtropical Water (NPSW) and North Pacific Intermediate Water (NPIW). The seawater mass stratification in the Lombok Strait based on temperature, salinity and density which are seen to follow the internal tidal pattern. The average values for energy dissipation and vertical diffusivity for each layer and replication were 5.73 x 10-7 W.Kg-1 and 3.67 x 10-2 m2.s-1 for CTD Yoyo and 2.25 x 10-6 W.Kg-1 and 7.38 x 10-2 m2.s-1 for CTD Snapshot. The value obtained is greater than the open ocean and straits in other studies. The high shear value confirms this in the thermocline layer. The Richardson gradient value> 0.25 is relatively constant in the thermocline layer.